POLITICAL DISCOURSE: OBAMAÃ¢â¬â¢S APPRAISAL ATTITUDE - Priyatmojo, Arif Suryo (Language Circle: Journal of Language and Literature, 2011)
This study aims at describing the way Obama gives appraisal attitude in his political view infront of his people of the United States in particular and people of the world in general. Theobject of the study was Obamas Inauguration Speech 2009 as the 44th president of the UnitedStates in the level of words, phrases, clauses and sentences. The data was analyzed usingAppraisal Attitude System (AAS). The result of the study shows that Obama believes thatAmerica is in an intricate position since it has many problems and some countries do not trustAmerica from the political perspective. Obama convinces his people by persuading them thathe can solve the problems in good ways.